High-throughput stem cell-based phenotypic screening through microniches. (4th July 2019) - Kolb, Laura; Allazetta, Simone; Karlsson, Maria; Girgin, Mehmet; Weber, Wilfried; Lutolf, Matthias P.
Abstract : Methods for screening combinations of signals for their effects on stem cell behavior are needed in the field of tissue engineering. We introduce a microgel-based screening platform for testing combinations of proteins on stem cell fate. Abstract : As the field of tissue engineering develops, methods for screening combinations of signals for their effects on stem cell behavior are needed. We introduce a microgel-based screening platform for testing combinations of in situ -generated proteins on stem cell fate in ultrahigh-throughput. Compartmentalizing individual sets of growth factors was addressed by encapsulating aggregates of stable recombinant cell lines secreting individual glycoproteins into microgels through an on-chip polymerization. When these 'microniches' are cultured with a cell type of interest, fluorescence reporters indicate positive niches that perform the desired function, and the underlying producer cell lines of these selected microniches are analyzed by barcoded RNA sequencing. The microniche-based screening work-flow was validated via a model system based on engineered mammalian cells expressing yellow fluorescent protein (YFP) upon anti-inflammatory cytokine interleukin 4 (IL4)-based activation.